2018
DOI: 10.1016/j.neubiorev.2018.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic coupling between the central and autonomic nervous systems during sleep: A review

Abstract: Sleep is characterized by coordinated cortical and cardiac oscillations reflecting communication between the central (CNS) and autonomic (ANS) nervous systems. Here, we review fluctuations in ANS activity in association with CNS-defined sleep stages and cycles, and with phasic cortical events during sleep (e.g., arousals, K-complexes). Recent novel analytic methods reveal a dynamic organization of integrated physiological networks during sleep and indicate how multiple factors (e.g., sleep structure, age, slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(163 citation statements)
references
References 173 publications
(251 reference statements)
8
155
0
Order By: Relevance
“…Nonetheless, BOLD signal results from a complex interplay between neuronal and vascular events (Friston et al, 2000, Obrig et al, 2000, Logothetis et al, 2001, Shmueli et al, 2007, Bianciardi et al, 2009, Webb et al, 2013, Yuan et al, 2013, Rayshubskiy et al, 2014, Chang et al, 2016, Tong et al, 2016, where oscillations in the signal could be affected by vasomotion (~0.1 Hz intrinsic fluctuations in arteriole diameter) or by autonomous nervous system activity (cardiac or respiratory activity). Notably, dynamic coupling between cardiac activity and spindle or slow wave activity has been reported during human sleep (Lechinger et al, 2015, Lin et al, 2016, Menson et al, 2016, de Zambotti et al, 2018, which predicts the post-sleep improvements in cognitive performances (Naji et al, 2018), consistent with the visceral influences on brain and behavior observed during wake (Critchley andHarrison, 2013, Park et al, 2014). Moreover, vasomotion is entrained by neuronal oscillations of similar frequency (Mateo et al, 2017).…”
Section: Potential Mechanisms Underlying Bold Oscillations In Sleepmentioning
confidence: 72%
“…Nonetheless, BOLD signal results from a complex interplay between neuronal and vascular events (Friston et al, 2000, Obrig et al, 2000, Logothetis et al, 2001, Shmueli et al, 2007, Bianciardi et al, 2009, Webb et al, 2013, Yuan et al, 2013, Rayshubskiy et al, 2014, Chang et al, 2016, Tong et al, 2016, where oscillations in the signal could be affected by vasomotion (~0.1 Hz intrinsic fluctuations in arteriole diameter) or by autonomous nervous system activity (cardiac or respiratory activity). Notably, dynamic coupling between cardiac activity and spindle or slow wave activity has been reported during human sleep (Lechinger et al, 2015, Lin et al, 2016, Menson et al, 2016, de Zambotti et al, 2018, which predicts the post-sleep improvements in cognitive performances (Naji et al, 2018), consistent with the visceral influences on brain and behavior observed during wake (Critchley andHarrison, 2013, Park et al, 2014). Moreover, vasomotion is entrained by neuronal oscillations of similar frequency (Mateo et al, 2017).…”
Section: Potential Mechanisms Underlying Bold Oscillations In Sleepmentioning
confidence: 72%
“…In physiological conditions, cardiac autonomic control fluctuates during sleep stages, with a predominant vagal modulation during NREM sleep and a sympathetic overactivity during REM (Benarroch, ; Busek et al., ; Ferri et al., ; Rossi et al., ; Tobaldini, Nobili et al., ; de Zambotti et al., ). However, data on autonomic control during sleep after acute ischaemic stroke are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Central control of the autonomic nervous system implicates a widespread cortical and subcortical network, including the bilateral insular cortex, anterior cingulate gyrus, amygdala and hypothalamus (Beissner, Meissner, Bär, & Napadow, ; Benarroch, ; Hilz et al., ; Ozdemir & Hachinski, ; Rossi, Santarnecchi, Valenza, Ulivelli, & Rossi, ; Verberne & Owens, ; de Zambotti, Trinder, Silvani, Colrain, & Baker, ). The insula has a prominent role and stroke affecting the insula (especially on the right side) is associated with elevated cardiac troponin, electrocardiogram (ECG) changes (altered repolarization phase and prolonged QTc) and cardiac arrhythmias (Abboud, Berroir, Labreuche, Orjuela, & Amarenco, ; Christensen, ; Colivicchi, Bassi, Santini, & Caltagirone, ; De Raedt et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these pathways activate the cortex and contribute to the low-voltage, high-frequency electroencephalogram (EEG) pattern occurring during wakefulness. Glutamatergic neurons in the parabrachial nucleus of the rostral pons are preferentially active during wakefulness [15, 16]; projections from the parabrachial nucleus to the NTS may represent a mechanism for adjusting BP between wakefulness and sleep. Increased parabrachial nucleus activity may inhibit the baroreflex [17–19], representing a mechanism for maintaining higher BP during wakefulness compared with sleep.…”
Section: Cardiorespiratory Regulation and Cns Activities During Wakefmentioning
confidence: 99%